Psychological Impact of the COVID-19 Pandemic on Children and Adolescents With and Without Mental Disorders - Gilsbach, Susanne; Herpertz-Dahlmann, Beate; Konrad, Kerstin (Frontiers in Public Health, 2021)
Background Previous and current studies highlight the psychological distress caused by COVID-19-associated restrictions among the general population, especially among children and adolescents; however, few studies have examined children and adolescents with a mental disorder. The current study aims to explore whether youth with mental disorders show a higher pandemic-associated psychological burden than healthy children and adolescents and to determine which psychiatric diagnoses are particularly associated with a higher distress level. Methods 144 children and adolescents between the ages of 6 – 18 years with a mental disorder and 48 children and adolescents within the same age range without a mental disorder, and their caregivers, completed questionnaires assessing pandemic-associated trauma symptoms (the Child Report of Post-Traumatic Symptoms (CROPS) and the Parents Report of Post-Traumatic Symptoms (PROPS)). Additionally, we asked specific questions about pandemic-associated stress factors, such as financial problems, prolonged screen times or loneliness. Results Children and adolescents with a mental illness showed a significantly higher psychological burden than mentally healthy peers. Female gender was a risk factor for a higher self-reported psychological burden, and a younger age was associated with a more extensive parent-reported psychological burden. Patients with a depressive disorder showed significantly higher levels of psychological distress associated with the COVID-19 pandemic than patients with an attention-deficit and/or a conduct disorder. Conclusions Children and adolescents with a mental illness, particularly females and individuals with a depressive disorder, are at an increased risk of suffering from pandemic-associated psychological distress. Adequate mental health care options, such as telepsychiatry, are indispensable.